Characterization of igf1 and igf2 genes during maraena whitefish (Coregonus maraena) ontogeny and the effect of temperature on embryogenesis and igf expression. (June 2018) - Nipkow, Mareen; Wirthgen, Elisa; Luft, Peter; Rebl, Alexander; Hoeflich, Andreas; Goldammer, Tom
Abstract: The insulin-like growth factors IGF-1 and IGF-2 play important roles in the growth, development, and metabolism of teleost fish. We isolated cDNA sequences of igf1, and igf2 genes from maraena whitefish. We quantified the mRNA and protein expressions of IGFs in different tissues of marketable juvenile maraena whitefish. Moreover, we analyzed the gene expression profiles during maraena whitefish development from unfertilized egg to fingerling and examined the effect of incubation temperature on igf1, and igf2 gene expression during embryonic and early larval development. Transcripts encoding IGF-1 or IGF-2 were detected in all tested tissues, with the greatest abundance in the liver. We measured higher igf2 than igf1 copy numbers in all tissues and at all developmental stages examined, even at advanced juvenile stages. Using the Western blot technique, we demonstrated that several isoforms of IGF-1 are expressed in the liver and gills but not in muscle tissue, indicating tissue-specific protein expression of IGF-1. We observed an accelerated embryonic development with increasing temperature, resulting in shortened hatching periods. Out of the three tested temperatures, we observed the highest hatching rate, larval hatching size, and larval growth at 6 °C. At 9 °C, hatching rate, larval hatching size and larval growth were reduced compared to the values we observed at 4 °C and 6 °C, since incubation temperature might have exceeded the optimum. To our knowledge, our data show for the first time that both igf1 and igf2 expression were upregulated due to elevated incubation temperature within embryonic development of fish. Further, we found significantly higher igf expression for the best-developing larvae (6 °C group) at specific life stages of maraena whitefish. Highlights: igf1 and igf2 cDNA sequences were identified in maraena whitefish liver is the major site of igf mRNA expression higher gene expression of igf2 than igf1 in tissues and during developmental stages increased temperature correlate with accelerated embryonic development and shortened hatching periods 6 °C incubation temperature improved hatching rate, larval hatching size and growth, and igf1 and igf2 expression were upregulated due to elevated incubation temperature